Monetary Policy and Sustainability - Martin Hellwig (Wirtschaftsdienst)
Abstract ECB President Christine Lagarde and others have suggested that climate change creates risks for price stability and for the viability of counterparties to central bank interventions and therefore monetary policy should contribute to fighting climate change. However, pursuit of this new objective may occassionally conflict with price stability, in which case the legal mandate as well as the underlying rationale for this mandate and for ECB independence call for prioritising price stability. However, monetary policy will have a sustainability problem of its own if the viability of the monetary system is threatened by financial and fiscal instability.